2012
DOI: 10.1074/jbc.m112.348300
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation of Tau Induced by Naturally Secreted Amyloid-β at Nanomolar Concentrations Is Modulated by Insulin-dependent Akt-GSK3β Signaling Pathway

Abstract: Alzheimer disease (AD) is neuropathologically characterized by the formation of senile plaques from amyloid-β (Aβ) and neurofibrillary tangles composed of phosphorylated Tau. Although there is growing evidence for the pathogenic role of soluble Aβ species in AD, the major question of how Aβ induces hyperphosphorylation of Tau remains unanswered. To address this question, we here developed a novel cell coculture system to assess the effect of extracellular Aβ at physiologically relevant levels naturally secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 45 publications
3
69
0
2
Order By: Relevance
“…These two central observations suggest that insulin signalling impacts on at least two parts of the proposed canonical amyloid cascade pathway of AD and evidence from in vitro studies, supporting such a suggestion, find that insulin protects neurons from Ab-induced phenotypes [21,22]. One remarkable observation from experimental studies in rodents, however, is that this cascade initiated by Ab oligomers and resulting in tau phosphorylation and aggregation does not occur in vivo.…”
Section: Diabetes and Ad: From Populations To Experimental Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…These two central observations suggest that insulin signalling impacts on at least two parts of the proposed canonical amyloid cascade pathway of AD and evidence from in vitro studies, supporting such a suggestion, find that insulin protects neurons from Ab-induced phenotypes [21,22]. One remarkable observation from experimental studies in rodents, however, is that this cascade initiated by Ab oligomers and resulting in tau phosphorylation and aggregation does not occur in vivo.…”
Section: Diabetes and Ad: From Populations To Experimental Modelsmentioning
confidence: 91%
“…Insulin decreases tau phosphorylation via inhibition of GSK3 [18,19] Insulin alters APP proteolytic cleavage [20] Insulin protects neurons against Ab toxicity [21,22] Insulin regulates IDE expression; mice lacking IDE have decreased rates of insulin and Ab degradation, exhibit brain Ab accumulation and develop hyperinsulinaemia [59] Ab modulates IIS in the brain by binding to IRs and disrupting signalling capacity leading to reduced surface expression of IRs and promotion of synaptic loss [63,64] Upregulation of IIS genes in a mouse model of amyloidosis as a possible means for neuroprotection [23] Lack of IRS2 is associated with increased tau phosphorylation and cognitive impairment [24,25] In vitro and in vivo evidence…”
Section: A) Impact On Ab and Tau Pathologymentioning
confidence: 99%
“…More specifically, levels of Akt and phospho-Akt, as well as Akt activity, were all reported to be decreased relative to controls [31]. Furthermore, the Akt signaling pathway has been shown to modulate the hyperphosphorylation of tau induced by nanomolar concentrations of naturally secreted amyloid-β [32], although hyperphosphorylation of tau can be promoted by many additional factors [33]. We found that GP up-regulates Akt and Bcl2, and down-regulates FOXO3 and P53.…”
Section: Discussionmentioning
confidence: 72%
“…Treating cells with the insulin-sensitizing drug rosiglitazone attenuated the Aβ-dependent hyperphosphorylation of Tau [39].…”
Section: Tau Hyperphosphorylation and Insulin Resistance Via Pparsmentioning
confidence: 97%